Constructing Gender Equality in Salaf Pesantren - Ellyda Retpitasari; Maulida Rohmatul Laili (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2026)
Discussions on gender equality continue to evolve and warrant further research in various settings, one of which is religious educational institutions such as pesantren (Islamic boarding school). The concept of gender equality is often perceived as conflicting with the Pesantren Salafiyah model, which typically features an authoritarian, conservative, and patriarchal culture. The objective of this study is to examine how gender equality is constructed at the Pesantren Salafiyah Kapurejo in Kediri Regency. The approach used in this study is a descriptive qualitative approach that examines the construction of gender equality in social interactions within the pesantren from the perspectives of students, teachers, and the pesantren leader (Kiai). Data were collected through observation, in-depth interviews, and documentation at the Pesantren Salafiyah Kapurejo, Kediri Regency, East Java. This study involved 14 informants, consisting of boarding school administrators, teachers, and male and female students. The results indicate that gender equality values have developed unevenly within the pesantren environment. First, in the externalization sphere, a culture of gender equality has been established through pesantren regulations and daily activities that provide relatively equal opportunities for male and female students to participate in learning, organizational activities, and decision-making. Second, in the internalization sphere, these values have been accepted and practiced by members of the pesantren community, as reflected in cooperation, tolerance, and the division of responsibilities based on competence, not gender. However, in the realm of objectification, the institutionalization of gender equality remains limited. Although pesantren formally promote equal treatment, these values have not yet been fully embedded in organizational structures, written policies, or leadership arrangements; consequently, the implementation of equality still relies heavily on individual awareness and informal practices rather than on permanent institutional mechanisms. Abstract IndonesianWacana tentang kesetaraan gender terus berkembang dan layak untuk diteliti di berbagai ruang, salah satunya adalah lembaga pendidikan berbasis agama seperti pesantren. Konsep kesetaraan gender sering dianggap bertentangan dengan konsep pesantren salaf yang umumnya memiliki budaya otoriter, konservatif, dan patriarkal. Tujuan untuk mengetahui bagaimana kesetaraan gender dikonstruksi di Pesantren Salafiyah Kapurejo, Kabupaten Kediri. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif deskriptif yang mengkaji konstruksi kesetaraan gender dalam interaksi sosial di pesantren dari perspektif santri, guru, dan pimpinan pesantren (Kiai). Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi di Pesantren Salafiyah Kapurejo, Kabupaten Kediri, Jawa Timur. Penelitian ini melibatkan 14 informan, yang terdiri dari pengasuh pesantren, guru, dan santri. Hasil penelitian menunjukkan bahwa nilai-nilai kesetaraan gender berkembang secara tidak merata di pesantren. Pertama, di ruang eksternalisasi, budaya kesetaraan gender telah terbentuk melalui peraturan pesantren dan kegiatan sehari-hari yang memberikan kesempatan yang relatif sama bagi santri laki-laki dan perempuan untuk berpartisipasi dalam pembelajaran, kegiatan organisasi, dan pengambilan keputusan. Kedua, di ruang internalisasi, nilai-nilai ini telah diterima dan dipraktikkan oleh anggota komunitas pesantren, sebagaimana tercermin dalam kerja sama, toleransi, dan pembagian tanggung jawab berdasarkan kompetensi, bukan gender. Namun, dalam ruang objektivasi, institusionalisasi kesetaraan gender masih terbatas. Meskipun pesantren secara formal mempromosikan perlakuan yang setara, namun nilai-nilai ini belum sepenuhnya tertanam dalam organisasi, kebijakan tertulis, atau pengaturan kepemimpinan, sehingga implementasi kesetaraan masih sangat bergantung pada kesadaran individu dan praktik informal daripada mekanisme kelembagaan yang permanen.